A study on the relationship between work environment and job performance at FGV Agri Services Sdn. Bhd, Jengka, Pahang / Shazwanie Mohd Latifi - Mohd Latifi, Shazwanie (2020)
This research paper's main objective was to investigate the relationship between work environment and job performance at FGV Agri Services Sdn Bhd, located in Pusat Penyelidikan Pertanian Tun Razak (PPPTR), Jengka Pahang. The aim of this research paper is also to measure the relationship between employee work environment and job performance. Questionnaire was being used as the instrument to collect data needed in order to complete this research paper. SPSS V-26 was used to analyze the questionnaire in order to determine the findings of the research. 32 out of 35 employees of FGV Agri Services were chosen as the respondents in the research conducted. The researcher was using table from Krejcie and Morgan (1970) in order to determine the sample size. This research paper used simple random sampling as the sampling technique. This research also has three research objectives and three research questions. A hypotheses were developed and tested using Pearson Correlation. There have relationship between work environment and job performance. The findings show high positive relationship between work environment and job performance at FGV Agri Services. Based on the findings of this research, the level of physical work environment is high with mean 3.968. Furthermore, this research found that the level of non-physical work environment is high with mean 3.984. Besides, the result shows that there is a high positive significant relationship exist between work environment and job performance, with the Pearson Correlation value which is 0.856. It realized at the end of the review that the work environment of the employee greatly have a positive relationship with job performance among employees in FGV Agri Services. The organization responsible for providing a comfortable working environment which will influence employees to work comfortably and to perform their job.